Kajian Literatur: Faktor-Faktor yang Mempengaruhi Partisipasi Pasien dalam Keselamatan Pasien - Wening Putri Susanti; Devi Nurmalia (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2021)
Introduction: Patient participation is globally recognized as one of the main factors for promoting quality and safety of health services. Active patient participation is a patient safety priority for health care. Yet, patients and their preferences are less understood. Literature review related to determinants of patient participation last five years is limited. The aim of this study was to determine the factors that influence patients to participate in patient safety. Methods: This study used a literature review method by searching online data. Literature was searched through electronic database such as EBSCOhost, Science Direct, and Scopus. The inclusion criteria of article were respondent to the article found are inpatient and nurse, full text articles and publication years from 2015 to 2019.Results: Search results found four articles were eligible to be reviewed. This review indicates that there are two factors that influence patient participation in patient safety, including factors from the patient's side and factors from the nurse's side.Conclusion: These results reinforce that creating patient safety requires the collaboration of all parties, not only from the nurse but also from the patient. Patient involvement needs to be further investigated regarding the extent of patient participation in patient safety.